Degree of technical difficulty of thyroidectomy for autoimmune thyroid disease. Issue 2 (25th October 2019) - Saadi, Robert; Brandt, Alyssa; Kim, Yesul; Cottrill, Elizabeth; Saunders, Brian; Schaefer, Eric; Goldenberg, David
Abstract: Background: Our goal was to elucidate the differences in degree of technical difficulty of thyroidectomy in patients with autoimmune thyroid diseases. Methods: Charts of adult patients who had undergone thyroidectomy were reviewed. Patients with Hashimoto's Thyroiditis (HT) or Graves' Disease (GD) were individually compared to a control group of patients with early stage malignancy or goiter. Results: The HT (n = 65) group was significantly more likely to have friable ( P = .001) and fibrotic ( P < .001) thyroids, longer operative times ( P = .02), and a 22‐modifier ( P = .005). The GD (n = 169) group was significantly more likely to have friable ( P < .001), vascular ( P < .001), fibrotic ( P = .038), and heavy ( P = .002) thyroids, longer operative times ( P = .03), increased length of stay ( P = .01) and a 22‐modifier ( P = .01). Conclusion: Our experience at an institution with a high‐volume thyroid practice demonstrates that patients with autoimmune thyroid disease have consistent qualitative changes of the thyroid and significantly increased operative times and surgical difficulty.